A LINGUISTIC LOOK AT STRATEGIC CHARACTER OF ENGLISH PROVERBS - Turaeva Oydinoy (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
This article investigates the communicative functions of English proverbs, emphasizing their role beyond mere expressions of folk wisdom. Proverbs are shown to function as effective tools for indirectness, persuasion, politeness, and cultural alignment. By examining their pragmatic and rhetorical roles in discourse, the study uncovers how these sayings enhance communication through subtlety, conciseness, and cultural resonance. The analysis draws on linguistic and pragmatic theories to highlight the value of proverbs in maintaining social harmony and conveying complex messages in everyday speech.